POTENSI SPORT TOURISM DALAM MENDONGKRAK EKONOMI KERAKYATAN - Purwanto, Edi; Pujianto, Agus; Pujianti, Amin (YLPK Mahardhika, 2024)
This study discusses the role of the Indonesian Community Recreation Sports Committee (KORMI) in developing sport tourism in Central Java. Sports tourism is a combination of sports and tourism that can enhance community participation and regional economic growth. The research employs a qualitative approach with descriptive-analytical methods to describe phenomena, analyze impacts, and identify challenges and opportunities in developing sport tourism. The results indicate that KORMI plays a strategic role in managing and popularizing community-based sports through sports events at tourist destinations, which can increase tourist visits, support local small and medium-sized enterprises (SMEs), and create job opportunities. However, the development of sports tourism in Central Java still faces infrastructure and promotion challenges, which need improvement. This study recommends strengthening collaboration between the government, the private sector, and the community to optimize the potential of sport tourism in Central Java.